2018
DOI: 10.1038/s41598-018-29163-6
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Aggravates the Activity of Periodontal Disease by Disrupting Redox Homeostasis- An Observational Study

Abstract: The aim of this study was to evaluate the associations between cigarette use and five salivary oxidative stress biomarkers, copper-zinc superoxide dismutase (Cu/Zn SOD), manganese superoxide dismutase (MnSOD), catalase, thioredoxin-1 (TRX1), and peroxiredoxin-2 (PRX2), to assess the effectiveness of non-surgical periodontal therapy. Materials and Methods: This is an observational study,167 patients diagnosed with periodontitis were recruited. Both saliva samples and clinical measurements (plaque index (PI), bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
4
25
0
8
Order By: Relevance
“…There is growing indication that smoking tobacco is a well-recognized component cause of both periodontal and periimplant inflammatory disorders and is the second well-known of the modifiable risk factors after microbial dental plaque. [1][2][3] It is indicated that tobacco smoking is associated with a substantial risk for soft tissue destruction and alveolar bone loss, depending mainly on the dosage, frequency, and level of disease severity. 4 Smoking has been shown to impair several features of the innate and adaptive host immune responses as exhaustively documented in numerous laboratory-based studies of tobaccorelated soft tissue destruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing indication that smoking tobacco is a well-recognized component cause of both periodontal and periimplant inflammatory disorders and is the second well-known of the modifiable risk factors after microbial dental plaque. [1][2][3] It is indicated that tobacco smoking is associated with a substantial risk for soft tissue destruction and alveolar bone loss, depending mainly on the dosage, frequency, and level of disease severity. 4 Smoking has been shown to impair several features of the innate and adaptive host immune responses as exhaustively documented in numerous laboratory-based studies of tobaccorelated soft tissue destruction.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing indication that smoking tobacco is a well‐recognized component cause of both periodontal and periimplant inflammatory disorders and is the second well‐known of the modifiable risk factors after microbial dental plaque . It is indicated that tobacco smoking is associated with a substantial risk for soft tissue destruction and alveolar bone loss, depending mainly on the dosage, frequency, and level of disease severity .…”
Section: Introductionmentioning
confidence: 99%
“…Studies [1][2][3][4] have shown that tobacco-smoking is a prospect of periodontal and peri-implant diseases, such as periodontitis and periimplantitis, respectively. Furthermore, outcomes of oral surgical interventions are undermined in tobacco smoking users compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies have demonstrated a definitive link between smoking and colorectal carcinogenesis such as MSI, CIMP, and a serrated pathway, which occur most often in the proximal colon 48,49 . Meanwhile, smoking increases the abundance of periodontal pathogen including Fusobacterium and Bacteroides , as well as the severity of periodontitis 28,51,52 , which might explain another mechanism that smoking affects the development of proximal CRNs via periodontal pathogen related gut dysbiosis 26,47 .…”
Section: Discussionmentioning
confidence: 99%